Iglesia Luterana Salvadoreña: el desafio de ser iglesia en un nuevo contexto de paz - Girón, Sigfrido Vladimir Hernández (2013)
The lutheran church in El Salvador is the product of the missionary work of the lutheran synod of Missouri, its further development has been a challenge to their authority, in the first part deals with the emergence of the salvadoran state from the years before the conquest, to the colony, where there was a large part of their religious tradition, independence from Spain until the war with its neighboring Honduras, in those years lutheranism arrives and founded the first churches. The structure adopted and its position in relation to the civil war ending this first part. The second part is a review of the road that followed the signing of the peace that ended the conflict, the structure adopted in the period of peace and the problems it faces in relation to resources and his flock, his conception of theology of life and its relationship to social movement, the new challenges facing in relation to their identity and social violence. The third and last part refers to the opportunity in the midst of the crisis, the social mission of the church; it s diaconal as part of practical theology, strategic planning in view of its future, ending with the democratic commitment and relationships participatory addition to possible ways forward.